2012
DOI: 10.1371/journal.pone.0046425
|View full text |Cite|
|
Sign up to set email alerts
|

In Vivo Tumorigenesis Was Observed after Injection of In Vitro Expanded Neural Crest Stem Cells Isolated from Adult Bone Marrow

Abstract: Bone marrow stromal cells are adult multipotent cells that represent an attractive tool in cellular therapy strategies. Several studies have reported that in vitro passaging of mesenchymal stem cells alters the functional and biological properties of those cells, leading to the accumulation of genetic aberrations. Recent studies described bone marrow stromal cells (BMSC) as mixed populations of cells including mesenchymal (MSC) and neural crest stem cells (NCSC). Here, we report the transformation of NCSC into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 39 publications
5
23
0
Order By: Relevance
“…Stress‐tolerant cell clusters of isolated skin fibroblasts or bone marrow stromal cells can differentiate into non‐tumorigenic endodermal, ectodermal, and mesodermal cells in vivo (Kuroda et al , ). Although mesenchymal stem cells are generally considered to be non‐tumorigenic, bone marrow stromal cells comprise a mixed population that includes neural crest stem cells and has potential tumorigenicity after long‐term in vitro passage (Wislet‐Gendebien et al , ). Recent studies have also reported that a human oral mucosa stem cell population expressing neural crest stem cell markers formed ectodermal‐ and mesodermal‐derived mixed tumors in severe combined immune deficiency mice (Marynka‐Kalmani et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Stress‐tolerant cell clusters of isolated skin fibroblasts or bone marrow stromal cells can differentiate into non‐tumorigenic endodermal, ectodermal, and mesodermal cells in vivo (Kuroda et al , ). Although mesenchymal stem cells are generally considered to be non‐tumorigenic, bone marrow stromal cells comprise a mixed population that includes neural crest stem cells and has potential tumorigenicity after long‐term in vitro passage (Wislet‐Gendebien et al , ). Recent studies have also reported that a human oral mucosa stem cell population expressing neural crest stem cell markers formed ectodermal‐ and mesodermal‐derived mixed tumors in severe combined immune deficiency mice (Marynka‐Kalmani et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…This procedure, necessary for the clinical application of hMSCs, is associated to the potential risk of cell immunogenicity, with issues of biosecurity regarding components of the culture medium and FBS, as well as the possibility of in vitro transformation of hMSCs [7]. High susceptibility to malignant transformation of MSCs has been described in animal models using stem cells isolated from the bone marrow of mice and monkeys, some becoming highly tumorigenic after in vitro culture, since they caused tumors in mice at sites where these cells were infused [91][92][93][94][95][96][97][98]. A recent study reported that differentiated hMSCs isolated from human bone marrow became tumorigenic in diabetic mice.…”
mentioning
confidence: 99%
“…Current literature is lacking for in vivo neoplastic differentiation of proven non-neoplastic MSC/ADSC, but Wislet-Gendebien et al retrospectively noted that one of the clones of the neural crest stem cells derived from bone marrow aspiration resulted in tumorigenesis in vivo after long-term in vitro passaging [47]. This specific clone surprisingly had the highest ability to differentiate into neuronal cells ( in vitro ), and also showed a very high rate of proliferation after injection into mice striatum, when compared to the other clones.…”
Section: Discussionmentioning
confidence: 99%